2021
DOI: 10.3233/jad-201204
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic, Phenotypic, and Neuropathological Characterization of the Tg4-42 Mouse Model for Alzheimer’s Disease

Abstract: Background: Preclinical Alzheimer’s disease (AD) research strongly depends on transgenic mouse models that display major symptoms of the disease. Although several AD mouse models have been developed representing relevant pathologies, only a fraction of available mouse models, like the Tg4-42 mouse model, display hippocampal atrophy caused by the death of neurons as the key feature of AD. The Tg4-42 mouse model is therefore very valuable for use in preclinical research. Furthermore, metabolic biomarkers which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Synaptic hyperactivity of hippocampal pyramidal neurons is therefore an early event in AD pathology. 18 F-Fluorodeoxyglucose ( 18 F-FDG)-PET in combination with magnetic resonance imaging (MRI) in Tg4–42 mice was used for analyzing cerebral brain glucose metabolism in vivo (Hinteregger et al, 2021 ). Tg4–42 mice demonstrated lower glucose uptake correlating with neuron loss and memory deficits in an age-dependent manner (Bouter et al, 2018 ).…”
Section: Chronic Effect Of N-truncated Aβ 4–42mentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic hyperactivity of hippocampal pyramidal neurons is therefore an early event in AD pathology. 18 F-Fluorodeoxyglucose ( 18 F-FDG)-PET in combination with magnetic resonance imaging (MRI) in Tg4–42 mice was used for analyzing cerebral brain glucose metabolism in vivo (Hinteregger et al, 2021 ). Tg4–42 mice demonstrated lower glucose uptake correlating with neuron loss and memory deficits in an age-dependent manner (Bouter et al, 2018 ).…”
Section: Chronic Effect Of N-truncated Aβ 4–42mentioning
confidence: 99%
“…Moreover, small RNA sequencing of the microRNAome in the hippocampus of Tg4–42 mice revealed microRNAs involved in learning, memory function, and synaptic signaling (Bouter et al, 2020 ). Metabolic changes of the glutamate/4-aminobutyrate-glutamine axis correlated with neurological deficits, neurodegeneration, and elevated CSF levels of neurofilament light chain in aged Tg4–42 mice (Hinteregger et al, 2021 ). Tg4–42 mice harbor more than 20 copies of the transgene in exon 2 of the retinoic acid receptor β (RARB) leading to decreased expression of RARB, which could have an (at least partial) effect on the phenotype (Hinteregger et al, 2020 ).…”
Section: Chronic Effect Of N-truncated Aβ 4–42mentioning
confidence: 99%
“…The rTg4510 transgenic mouse, an increasingly popular AD model, reported severe hippocampal and neocortical atrophy with concomitant increased ventricles [ 137 ], where females had larger volume decrements than males and both sexes were reduced significantly compared to WT [ 138 ]. Other AD mouse models, such as ApoE4 (24 months), Tau4RDeltaK and Tg4–42 mice, also exhibited significant hippocampal and whole brain volume decrements [ 139 , 140 , 141 ].…”
Section: Magnetic Resonance Findings In Other Ad Mouse Modelsmentioning
confidence: 99%
“…The authors suggest that regional GABA levels may contribute to the sex disparities observed in AD; but this awaits further study. In a recently developed tau mouse model of AD, Tg4-42, reduced 4-aminobutyrate, Gln and lactate in the cortex were reported, with reductions in 4-aminobutyrate in the caudate putamen [ 139 ]. These reductions mirrored increased levels of metabolizing enzymes and increasing Aβ42 levels with increased neuroinflammation and neuronal loss [ 139 ].…”
Section: Magnetic Resonance Findings In Other Ad Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation